A triphenylamine derivative based on phenothiazine and its polymer and its preparation method and application

By introducing a phenothiazine structure into triphenylamine, a non-coplanar dendritic conductive polymer is constructed, and the problems of poor stability and low conductivity of triphenylamine derivatives are solved, and a high-performance electrochromic material is achieved.

CN116925008BActive Publication Date: 2025-04-22ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310887875.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-04-22
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

The existing triphenylamine and its derivatives are prone to decomposition and degradation under long exposure to light, heat and moisture, resulting in poor stability and low electrical conductivity.

Method used

A tripaniline derivative based on phenothiazine was developed to construct a non-coplanar dendritic structure by phenothiazine and tripaniline, thereby improving the spatial structure steric hindrance and polymerization of conductive polymers.

Benefits of technology

The electrochemical and thermodynamic stability of conductive polymer films is significantly improved, the electrochromic properties are enhanced, and the material shows multiple color changes at different voltages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116925008B_ABST
    Figure CN116925008B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of organic synthesis, and discloses a triphenylamine derivative based on phenothiazine and a polymer thereof, as well as a preparation method and application thereof. The invention provides a triphenylamine derivative based on phenothiazine through structural design, which has abundant active sites and is conducive to achieving a high degree of polymerization during the polymerization process, thereby constructing a conductive polymer film with a cross-linked structure, showing excellent electrochemical and thermodynamic stability. At the same time, the conductive polymer film has a loose surface morphology, which is conducive to the embedding and extraction of electrolyte ions in the conductive polymer material, thereby improving the electrochromic properties of the polymer film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic synthesis, and particularly relates to a triphenylamine derivative. Background Art

[0002] Electrochromism refers to the phenomenon that the optical properties (absorption, reflectivity and transmittance) of a material change reversibly under different voltages, which manifests itself as a reversible change in the color of the material on a macroscopic scale. Electrochromic technology has a very broad application prospect and has been applied to smart windows, anti-glare rearview mirrors for cars, electronic paper and military camouflage. However, materials are still one of the main bottlenecks limiting the application of electrochromic technology. The design and preparation of electrochromic materials with rich color changes, high optical contrast, fast response and high cycle stability are of great significance to the development of electrochromic technology.

[0003] As one of the main electrode materials of electrochromic supercapacitors, high molecular conductive polymer materials stand out among many electrochromic materials due to their advantages such as high specific capacity, high conductivity, easy synthesis, rich colors, and low cost during redox. Triphenylamine and its derivatives are a commonly used hole transport and electrochromic unit. Due to their excellent optoelectronic properties such as photoconductivity, electroluminescence, photochromism, and electrochromism, they have received great attention in the field of organic optoelectronic functional materials.

[0004] However, as a commonly used conductive polymer matrix material, triphenylamine and its derivatives are prone to decomposition and degradation when exposed to light, heat, moisture and other environments for a long time, thus affecting their service life. Compared with metals and other conductive materials, triphenylamine and its derivatives have lower conductivity and will undergo oxidation reaction under long-term exposure to air, further reducing their conductivity. Summary of the invention

[0005] In order to solve the problems of poor stability and low conductivity of triphenylamine and its derivatives in the prior art, the present invention provides a triphenylamine derivative based on phenothiazine and its polymer and its preparation method, as well as its application in the preparation of electrochromic materials and electronic devices. Phenothiazine is a commonly used electron donor unit with non-planarity. Based on triphenylamine and phenothiazine, a new conductive polymer monomer is developed to prepare a new conductive polymer material, and a high-performance electrochromic conductive polymer material is prepared.

[0006] The first aspect of the present invention provides a triphenylamine derivative based on phenothiazine, as shown in Formula I:

[0007]

[0008] Triphenylamine and its derivatives are commonly used hole transport materials and light-emitting units, while phenothiazine contains electron-rich sulfur atoms and nitrogen atoms, which are good donors. The phenothiazine ring is a non-planar structure, presenting a butterfly conformation, which can hinder molecular aggregation and the formation of intermolecular quasi-molecules. Compared with the existing triphenylamine and its derivatives, the triphenylamine derivatives based on phenothiazine provided by the present invention have a greater spatial structural advantage. First, the triphenylamine derivatives have more abundant active sites, and the conductive polymer film with a cross-linked structure is polymerized using it as a monomer, and has six polymerizable active sites during polymerization. Compared with the existing linear structure compounds, the triphenylamine derivatives based on phenothiazine are easier to prepare the corresponding cross-linked polymer film by electrochemical polymerization, have a higher degree of polymerization, and greatly improve the electrochemical and thermodynamic stability of the conductive polymer film. Another advantage is that the phenothiazine-based triphenylamine derivatives provided by the present invention are non-coplanar multi-branched structures. The non-planar structure of phenothiazine is conducive to breaking the planarity of the molecule. When preparing a conductive polymer film, the non-coplanarity of the molecules causes the connection between multiple monomers after polymerization to break the regularity of the polymer spatial structure, so that the prepared polymer has a loose and porous structure, and the polymer film has a looser surface morphology, which is conducive to the embedding and release of electrolyte ions in the conductive polymer material, thereby significantly improving the electrochromic properties of the polymer film.

[0009] The second aspect of the present invention provides a method for preparing the above-mentioned triphenylamine derivatives based on phenothiazine, comprising the following steps:

[0010] (1) reacting 10-phenyl-10H-phenothiazine represented by formula II with N-bromosuccinimide represented by formula III to obtain an intermediate represented by formula IV;

[0011] (2) coupling reaction of the intermediate represented by Formula IV with triphenylamine-4-boric acid represented by Formula V to obtain the phenothiazine-based triphenylamine derivative represented by Formula I;

[0012]

[0013] Furthermore, in the step (1), the reaction temperature is -5 to 25°C, preferably 0 to 25°C.

[0014] Preferably, in step (1), the molar ratio of 10-phenyl-10H-phenothiazine represented by formula II to N-bromosuccinimide represented by formula III is 1:8-10, preferably 1:9-10, and more preferably 1:9.

[0015] Preferably, in step (1), the reaction solvent is N,N-dimethylformamide. The volume amount of the reaction solvent is preferably 30 to 40 mL / g based on the mass of 10-phenyl-10H-phenothiazine.

[0016] Specifically, the preparation method of step (1) is preferably:

[0017] In step (1), 10-phenyl-10H-phenothiazine shown in formula II and N-bromosuccinimide shown in formula III are mixed, anhydrous N,N-dimethylformamide is added as a reaction solvent, and the mixture is stirred in an ice-water mixed bath for 6 to 8 hours. After the reaction is completed, the reaction solution is purified to obtain the intermediate 3Br-FSQ shown in formula IV. The reaction solution purification method is generally as follows: the reaction solution is poured into water, extracted with dichloromethane, the organic phase is concentrated and then dried, the sample is mixed with coarse silica gel, and then column chromatography is performed for purification, the eluent containing the target compound is collected, the solvent is removed by rotary evaporation and dried to obtain the intermediate 3Br-FSQ shown in formula IV. The column chromatography purification generally uses fine silica gel as the stationary phase and dichloromethane and petroleum ether in a volume ratio of 1:4 to 5 as the mobile phase.

[0018] Furthermore, in the step (2), tetrakis(triphenylphosphine)palladium is used as a catalyst. Tetrakis(triphenylphosphine)palladium is a coordination compound centered on palladium (Pd), which is formed by coordination of four triphenylphosphine ligands and palladium atoms. Tetrakis(triphenylphosphine)palladium is a common palladium complex with good catalytic activity and selectivity, and can catalyze the Suzuki coupling reaction between aromatic compounds and halogenated hydrocarbons.

[0019] The mass amount of the tetrakis(triphenylphosphine)palladium is 0.01-1% of the mass amount of the intermediate represented by formula IV, preferably 0.1%.

[0020] Furthermore, in the step (2), the molar ratio of the intermediate represented by formula IV to the triphenylamine-4-boric acid represented by formula V is 1:3-4, preferably 1:3.5-4, and more preferably 1:4.

[0021] Preferably, in step (2), tetrabutylammonium bromide is used as a reaction accelerator. The mass amount of the tetrabutylammonium bromide is 0.1-2% of the mass amount of the intermediate shown in formula IV, preferably 1%.

[0022] Preferably, in the step (2), the reaction solvent is selected from at least one of toluene and tetrahydrofuran, preferably a mixed solvent of toluene and tetrahydrofuran, the volume ratio of toluene to tetrahydrofuran in the mixed solvent is 1.5:1, and the volume amount of the mixed solvent is 30 to 40 mL / g based on the mass of the intermediate shown in Formula IV.

[0023] Preferably, the reaction in step (2) is carried out under nitrogen protection.

[0024] The reaction in step (2) is preferably carried out by heating to reflux.

[0025] Specifically, the preparation method of step (2) is preferably:

[0026] In step (2), under the protection of N2, the compound shown in formula IV, tetrabutylammonium bromide, and triphenylamine-4-boric acid are dissolved in a mixed solvent of toluene and tetrahydrofuran, and tetrakis(triphenylphosphine)palladium is used as a catalyst, and the mixture is heated to reflux for 18 to 24 hours. After the reaction is completed, the reaction solution is purified to obtain the target product 3TPAFSQ shown in formula I, that is, the triphenylamine derivative based on phenothiazine described in the present invention. The reaction solution is usually purified by: extracting with dichloromethane, concentrating the extract and drying it, mixing the sample with coarse silica gel, and then purifying it by column chromatography, collecting the eluate containing the target compound, and removing the solvent by rotary evaporation and drying it to obtain the target product 3TPAFSQ shown in formula I. The column chromatography purification generally uses fine silica gel as the stationary phase and dichloromethane and petroleum ether with a volume ratio of 1:4 to 5 as the mobile phase.

[0027] The coarse silica gel used for mixing samples is coarse-porous silica gel, also called C-type silica gel, which is a highly active adsorption material and an amorphous substance with a chemical formula of mSiO2·nH2O. The fine silica gel is fine-porous silica gel, which is a colorless or slightly yellow transparent glass. The basic quality parameters are as follows: average pore distance 2.0-3.0MM, specific surface area 650-800m 2 / g, pore volume 0.35~0.4mL / g, specific heat 0.92KJ / kg.℃, thermal conductivity 0.63KJ / m·hr.℃.

[0028] The third aspect of the present invention provides a use of a phenothiazine-based triphenylamine derivative in the preparation of an electrochromic material.

[0029] Specifically, the phenothiazine-based triphenylamine derivatives are used to prepare phenothiazine-based triphenylamine conductive polymers, and the phenothiazine-based triphenylamine conductive polymers are used to prepare electrochromic materials.

[0030] In a fourth aspect of the present invention, there is provided a phenothiazine-based triphenylamine conductive polymer using a phenothiazine-based triphenylamine derivative as a monomer, as shown in Formula VI:

[0031]

[0032] In Formula VI, n represents the average degree of polymerization, and n is 10-2000.

[0033] Specifically, the triphenylamine derivatives based on phenothiazine provided by the present invention are easy to prepare electrochromic materials by electrochemical polymerization. Specifically, the triphenylamine derivatives based on phenothiazine and the supporting electrolyte are dissolved in a solvent, and cyclic voltammetry electrochemical polymerization is performed to obtain a film, namely, a triphenylamine conductive polymer. The inventors tested the obtained compound film by ultraviolet-visible spectroscopy and electrochromic performance, and found that the polymer film is colorless and transparent in the neutral state, pink in the semi-oxidized state, and brown-black in the fully oxidized state, and has good electrochromic performance.

[0034] A fifth aspect of the present invention provides a method for preparing a triphenylamine-based conductive polymer based on phenothiazine, comprising the following steps:

[0035] S1: dissolving the phenothiazine-based triphenylamine derivative represented by formula I and a supporting electrolyte in a solvent;

[0036] S2: The phenothiazine-based triphenylamine derivatives shown in Formula I are polymerized into a film by a cyclic voltammetry electrochemical method to obtain the phenothiazine-based triphenylamine conductive polymer shown in Formula VI.

[0037] Preferably, in step S1, the supporting electrolyte is selected from at least one of tetrabutylammonium hexafluorophosphate, tetrabutylammonium perchlorate, lithium tetrafluoroborate, and lithium perchlorate, and more preferably tetrabutylammonium hexafluorophosphate. When tetrabutylammonium hexafluorophosphate is used as the supporting electrolyte, the preparation effect of the polymer is the best.

[0038] Preferably, in step S1, the solvent is selected from at least one of dichloromethane, acetonitrile, and propylene carbonate; more preferably, it is at least one of chromatographic grade dichloromethane, chromatographic grade acetonitrile, and chromatographic grade propylene carbonate, such as a mixed solvent of dichloromethane and acetonitrile in a certain proportion; most preferably, it is chromatographic grade dichloromethane. When chromatographic grade dichloromethane is used as the solvent, the preparation effect of the polymer is the best.

[0039] The supporting electrolyte and solvent should be flexibly selected and matched according to their properties.

[0040] The selection of solvents should take into account their solubility and conductivity, wherein the solubility is: dichloromethane > acetonitrile > propylene carbonate; the conductivity is: acetonitrile > dichloromethane > propylene carbonate. Preferably, the solvent is a mixed solvent of dichloromethane and acetonitrile in a certain proportion, which combines the advantages of good solubility of dichloromethane and high conductivity of acetonitrile.

[0041] For the selection of electrolyte, the soluble solvent of the electrolyte and its ionic radius should be considered. Among them, tetrabutylammonium hexafluorophosphate and tetrabutylammonium perchlorate can be dissolved in dichloromethane and acetonitrile among the above solvents, and lithium tetrafluoroborate and lithium perchlorate can be dissolved in acetonitrile and propylene carbonate; while the ionic radius of tetrabutylammonium hexafluorophosphate and tetrabutylammonium perchlorate is larger, and the ionic radius of lithium tetrafluoroborate and lithium perchlorate is smaller.

[0042] Furthermore, in the step S1, the concentration of the phenothiazine-based triphenylamine derivative represented by formula I is 0.5-1 mmol / L, and the concentration of the supporting electrolyte is 0.05-0.1 mol / L.

[0043] Furthermore, in step S2, the parameters of the cyclic voltammetry electrochemical method include: a voltage of 0 to 1.5 V, and a polymerization cycle of 11 to 15 cycles; the polymerization cycle is preferably 13 to 15 cycles, and more preferably 15 cycles. The polymerization cycle is proportional to the thickness of the prepared polymer film, and the greater the number of cycles, the thicker the polymer film. When the polymerization cycle is 15, the polymer film thickness is 200 nm, and its electrochromic performance is excellent.

[0044] Specifically, the preparation method of step S2 is preferably:

[0045] The phenothiazine-based triphenylamine derivative shown in formula I and a supporting electrolyte are dissolved in a solvent, and then a cyclic voltammetry electrochemical polymerization method is used with ITO glass as a working electrode, a platinum sheet as a counter electrode, and Ag / AgCl as a reference electrode to obtain a polymer film p3TPAFSQ shown in formula VI, i.e., the triphenylamine conductive polymer.

[0046] In the preparation process of the triphenylamine conductive polymer, specifically, after the cyclic voltammetry electrochemical polymerization film is formed, the polymer film is dedoped, cleaned and dried. Preferably, the dedoping condition is a voltage of -0.8 to -0.5 V and a time of 30 to 60 seconds. The liquid system used for cleaning is a chromatographic grade mixed solution of dichloromethane.

[0047] The sixth aspect of the present invention provides an application of a phenothiazine-based triphenylamine conductive polymer in the preparation of an electrochromic electronic device.

[0048] Specifically, the phenothiazine-based triphenylamine conductive polymer is used to prepare an electrochromic electrode.

[0049] The performance test method of the phenothiazine-based triphenylamine conductive polymer as an electrochromic electrode material is as follows: the electrolyte tetrabutylammonium hexafluorophosphate is dissolved in chromatographic grade dichloromethane and used as a blank supporting electrolyte solution. The blank electrolyte solution is used as the test solution, the polymer film is used as the working electrode, the platinum wire is used as the counter electrode, and Ag / AgCl is used as the reference electrode to form a three-electrode system to test the optical contrast of the triphenylamine conductive polymer and the cyclic voltammetry curve and UV-visible absorption spectrum at different voltages.

[0050] Compared with the prior art, the present invention has the following technical effects:

[0051] (1) The present invention constructs a phenothiazine-based triphenylamine derivative monomer by using phenothiazine and triphenylamine, which is a non-coplanar dendritic structure, bringing greater steric hindrance. At the same time, the dendritic non-planar structure can cause a certain structural distortion in the molecular structure. Compared with the existing linear structure compounds or X-type and Y-type structure compounds, the structure of the polymer film after polymerization is looser, the electrolyte ions are easier to embed and remove, and the color change response speed of the material is faster.

[0052] (2) The phenothiazine-based triphenylamine derivatives provided by the present invention have more polymerizable active sites during polymerization. The richer active sites make it easier for the monomers to be prepared by electrochemical polymerization to obtain the corresponding polymer film, and have a higher degree of polymerization, which greatly improves the electrochemical and thermodynamic stability of the conductive polymer film.

[0053] (3) The triphenylamine derivatives based on phenothiazine provided in the present invention have good reaction selectivity, a relatively simple preparation process, few by-products, easy separation and high final yield.

[0054] (4) The phenothiazine-based triphenylamine derivatives provided by the present invention can be used to prepare polymer films at a lower driving voltage through cyclic voltammetry electrochemical polymerization.

[0055] (5) The polymer film prepared by the present invention can show a variety of color changes under different voltages and has potential application value in the field of electrochromism. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 Infrared spectrum of the phenothiazine-based triphenylamine derivative 3TPAFSQ in Example 4.

[0057] Figure 2 It is the cyclic voltammetric polymerization curve of the phenothiazine-based triphenylamine derivative 3TPAFSQ in Examples 7-11.

[0058] Figure 3This is the cyclic voltammetry polymerization curve of the phenothiazine-based triphenylamine derivative 3TPAFSQ in Comparative Example 1.

[0059] Figure 4 This is a cyclic voltammetry curve of the polymer film p3TPAFSQ obtained by testing in Example 12 at different scan rates.

[0060] Figure 5 This is the UV-visible absorption spectrum of the polymer film p3TPAFSQ obtained by testing in Example 13 under different voltages.

[0061] Figure 6 This is the electrochromic optical contrast diagram of the polymer film p3TPAFSQ obtained by testing in Example 14.

[0062] Figure 7 This is the electrochromic optical contrast diagram of the polymer film p3TPAFSQ obtained by testing in Example 1.

[0063] Figure 8 This is the electrochromic optical contrast diagram of the polymer film p3TPACB obtained by testing in Example 2. DETAILED DESCRIPTION

[0064] The following is an explanation of the embodiments of the present invention by specific specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, in the absence of conflict, the features in the following embodiments and embodiments can be combined with each other. In the embodiments of the present invention, the methods used are all conventional methods unless otherwise specified, and the reagents used can be obtained from commercial sources.

[0065] [Preparation of the intermediate 3Br-FSQ shown in formula IV]

[0066] Embodiment 1:

[0067] 10-Phenyl-10H-phenothiazine (500 mg, 1.81 mmol) and NBS (2.89 g, 9.30 mmol) were added to a single-mouth round-bottom flask in sequence, and anhydrous N,N-dimethylformamide (20 mL) was added as the reaction solvent, and stirred at 0°C for 8 hours. After the reaction was completed, the reaction solution was poured into 400 mL of deionized water, vacuum filtered, and the filter cake was dissolved with 200 mL of dichloromethane, and anhydrous sodium sulfate was added to dry and remove water. After mixing the sample with coarse silica gel, column chromatography was performed for purification, with fine silica gel as the stationary phase, and dichloromethane and petroleum ether as the mobile phase. The eluent containing the target compound was collected, the solvent was removed by rotary evaporation and dried to obtain the pure product 3Br-FSQ with a yield of 90%. The NMR characterization structure of the product 3Br-FSQ is as follows: 1HNMR (400MHz, CDCl3) δ8.12 (d, J=2.3Hz, 2H), 7.94–7.83 (m, 2H), 7.57–7.48 (m, 2H), 7.30 (d, J=2.0Hz, 2H), 6.62 (d, J=9.1Hz, 2H). MS (ESI): [M+H]+509.8157.

[0068] Embodiment 2:

[0069] Compared with Example 1, the reaction temperature in Example 2 is -5°C, and the other steps are the same, and the pure product FSQ-3Br is obtained with a yield of 85%.

[0070] Embodiment 3:

[0071] Compared with Example 1, the reaction temperature in Example 3 is 25° C., and the remaining steps are the same, to obtain a pure product FSQ-3Br with a yield of 88%.

[0072] [Preparation of phenothiazine-based triphenylamine derivative 3TPAFSQ shown in formula I]

[0073] Embodiment 4:

[0074] 3Br-FSQ (500 mg, 0.98 mmol), triphenylamine-4-boric acid (991 mg, 3.43 mmol), tetrabutylammonium bromide (1 wt %), K2CO3 (3qe) and tetrakis(triphenylphosphine)palladium (0.1 wt %) prepared in Example 1 were added to a 100 mL two-necked round-bottom flask in sequence. Under N2 protection, toluene (15 mL) and tetrahydrofuran (10 mL) were added as reaction solvents. 3 ml of deionized water was added to the reaction flask, stirred, and heated under reflux at 80° C. for 48 hours. After the reaction was completed, it was extracted with dichloromethane three times. After the extract was concentrated, it was dried over anhydrous sodium sulfate to remove water. After mixing with coarse silica gel, it was purified by column chromatography with fine silica gel as the stationary phase and dichloromethane and petroleum ether as the mobile phase (dichloromethane: petroleum ether=1:1). The eluent containing the target compound was collected, the solvent was removed by rotary evaporation and dried to obtain the pure product 3TPAFSQ with a yield of 70%. The infrared spectrum of the product 3TPAFSQ is as follows Figure 1 shown.

[0075] Embodiment 5:

[0076] Compared with Example 4, the amount of triphenylamine-4-boric acid added in Example 5 is: 850 mg, 2.94 mmol, and the remaining steps are the same to obtain a pure product 3TPAFSQ with a yield of 52%.

[0077] Embodiment 6:

[0078] Compared with Example 4, the amount of triphenylamine-4-boric acid added in Example 6 is: 1.13 g, 3.92 mmol, and the remaining steps are the same to obtain a pure product 3TPAFSQ with a yield of 72%.

[0079] [Preparation of triphenylamine-based conductive polymer p3TPAFSQ based on phenothiazine as shown in formula VI]

[0080] Embodiments 7 to 11:

[0081] Example 7 provides a phenothiazine-based triphenylamine conductive polymer with a phenothiazine-based triphenylamine derivative as a monomer and a preparation method thereof. This example also provides an application of a phenothiazine-based triphenylamine derivative in the preparation of an electrochromic material triphenylamine conductive polymer.

[0082] 11.31 mg of 3TPAFSQ monomer prepared in Example 6 with a final concentration of 1 mmol / L was added to a 10 mL volumetric flask, 0.387 g of tetrabutylammonium hexafluorophosphate was added as a supporting electrolyte, and the volume was fixed with chromatographic grade dichloromethane. Ultrasonication was performed for 3 min. After the solid was completely dissolved, cyclic voltammetric electrochemical polymerization was performed. The specific process was as follows: ITO glass (0.9×4 cm) was used as the working electrode, platinum wire was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The polymerization voltage window was 0 to 1.5 V, and the number of polymerization cycles was 11 to 15 cycles. After the polymerization was completed, dedoping was performed in a 0.1 mol / L tetrabutylammonium hexafluorophosphate dichloromethane solution for 60 s (voltage -0.5 V), and then the polymer film was washed with chromatographic grade dichloromethane and dried at room temperature.

[0083] The cyclic voltammetry polymerization curve of the preparation process is as follows Figure 2 As shown. Figure 2 It can be seen that as the number of polymerization cycles increases, the peak current intensity of the polymer gradually increases, indicating that the polymer is successfully deposited on the ITO conductive glass. In Example 11, when the number of polymerization cycles is 15, the thickness of the polymer p3TPAFSQ film is 200 nm.

[0084] Comparative Example 1:

[0085] Compared with Example 11, when performing cyclic voltammetric electrochemical polymerization in Comparative Example 1, the number of polymerization cycles is 10, and the remaining steps are the same. The cyclic voltammetric polymerization curve of the preparation process is shown in FIG. Figure 3 As shown. Figure 3 It can be seen that as the number of polymerization turns increases, the peak current intensity of the polymer gradually increases, indicating that the polymer is successfully deposited on the ITO conductive glass. Compared with the polymer film with 15 polymerization turns obtained in Example 11, the peak current intensity of the polymer film with 10 polymerization turns obtained in Comparative Example 1 is less than that in Example 11, and the thickness of the polymer film is reduced to 132 nm.

[0086] Comparative Example 2:

[0087] Lv et al. provided a triphenylamine-based conductive polymer p3TPACB with the compound shown in formula A as a monomer. The preparation method of the polymer film is the same as that of Example 10.

[0088]

[0089] Lv, Xiaojingetal. "Acore–shellcompositeofporousZnOnanosheetsandamultichromic conductingpolymer:enhancedelectrochromicperformances." New Journal of Chemistry 38 (2014): 2400-2406.

[0090] [Application of triphenylamine-based conducting polymer p3TPAFSQ based on phenothiazine in the preparation of electrochromic electronic devices]

[0091] Example 12: Cyclic voltammetry test of polymer p3TPAFSQ thin film

[0092] This embodiment provides an application of a phenothiazine-based triphenylamine conductive polymer in the preparation of an electrochromic electrode.

[0093] 0.387 g of tetrabutylammonium hexafluorophosphate (TBA) with a final concentration of 0.1 mol / L was added to a 10 mL volumetric flask, and chromatographic grade dichloromethane was added to make up the volume. Ultrasonication was performed until the electrolyte was completely dissolved, and this was used as a blank supporting electrolyte solution. The conductive polymer film prepared in Example 11 was used as a working electrode, Ag / AgCl as a reference electrode, and a platinum wire as a counter electrode. The cyclic voltammetry curve of the polymer film at a voltage of 0 to 1.2 V was tested. The test results are shown in FIG. Figure 4 The scanning speeds are 10mV / s, 20mV / s, 30mV / s, 50mV / s, and 100mV / s respectively.

[0094] Depend on Figure 4 From the cyclic voltammetry curves at different scan rates, it can be seen that the polymer film is well deposited on the surface of the ITO conductive substrate, and the redox properties of the material are reversible and non-diffusion controlled.

[0095] Example 13: UV-Visible Absorption Spectrum Test of Polymer p3TPAFSQ Thin Film

[0096] This embodiment provides an application of a phenothiazine-based triphenylamine conductive polymer in the preparation of an electrochromic electrode.

[0097] 0.387 g of tetrabutylammonium hexafluorophosphate (0.1 mol / L in final concentration) was added to a 10 mL volumetric flask, and chromatographic grade dichloromethane was added to make up the volume. Ultrasonication was performed until the electrolyte was completely dissolved, and this was used as a blank supporting electrolyte solution. The conductive polymer film prepared in Example 11 was used as a working electrode, Ag / AgCl as a reference electrode, and platinum wire as a counter electrode. The UV-visible absorption spectrum of the polymer film at a voltage of 0 to 1.2 V was tested. The test results are shown in FIG. Figure 5 shown.

[0098] Depend on Figure 5 It can be seen from the UV-visible absorption spectrum that the polymer film is colorless and transparent in the neutral state, pink in the semi-oxidized state, brown-black in the fully oxidized state, and has good electrochromic properties.

[0099] Example 14: Electrochromic performance test of polymer p3TPAFSQ film

[0100] This embodiment provides an application of a phenothiazine-based triphenylamine conductive polymer in the preparation of an electrochromic electrode.

[0101] 0.387 g of tetrabutylammonium hexafluorophosphate (TBAFP) with a final concentration of 0.1 mol / L was added to a 10 mL volumetric flask, and chromatographic grade dichloromethane was added to make up the volume. Ultrasonication was performed until the electrolyte was completely dissolved, and this was used as a blank supporting electrolyte solution. The conductive polymer film prepared in Example 7 was used as a working electrode, Ag / AgCl as a reference electrode, and a platinum wire as a counter electrode. The optical contrast diagram of the polymer film was tested. The test results are shown in FIG. Figure 6 shown.

[0102] Depend on Figure 6 From the optical contrast diagram, it can be seen that the coloring time of the film at 485nm, 761nm and 1100nm are 1.66s, 3.24s and 2.85s respectively, and the fading time is 0.61s, 0.65s and 0.91s respectively. The optical contrast can reach 70.21%, 77.79% and 53.86% respectively, showing relatively good electrochromic performance.

[0103] Comparative Example 3:

[0104] Compared with Example 14, in Comparative Example 3, the polymer films provided in Comparative Example 1 and Comparative Example 2 are used as working electrodes instead of the polymer p3TPAFSQ film in Example 14. The remaining steps are the same. The optical contrast images of the polymer films provided in Comparative Example 1 and Comparative Example 2 are tested respectively. The test results are as follows: Figure 7 and Figure 8 shown.

[0105] Depend on Figure 7It can be seen that the optical contrast of the polymer p3TPAFSQ film with 10 polymerization circles provided in Comparative Example 1 is 58.70% at a wavelength of 761 nm, which is a decrease of 24.5% compared with the optical contrast of 77.79% in Example 11.

[0106] like Figure 8 As shown, by comparison, it is found that the optical contrast of the polymer p3TPAFSQ film provided in Example 11 is significantly higher than that of the polymer p3TPACB film in Comparative Example 2 in the visible light range, which indicates that the polymer p3TPAFSQ film provided in Example 11 has a more obvious color change, giving it a broader application prospect.

[0107] The embodiments described above are merely descriptions of preferred implementations of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope of the present invention.

Claims

1. A triphenylamine derivative based on phenothiazine, characterized in that: As shown in Formula I:

2. A method for preparing a triphenylamine derivative based on phenothiazine as claimed in claim 1, characterized in that: The following steps are involved: (1) reacting 10-phenyl-10H-phenothiazine represented by formula II with N-bromosuccinimide represented by formula III to obtain an intermediate represented by formula IV; (2) coupling reaction of the intermediate represented by Formula IV with triphenylamine-4-boric acid represented by Formula V to obtain the triphenylamine derivative based on phenothiazine represented by Formula I; 3. The method for preparing triphenylamine derivatives based on phenothiazine according to claim 2, characterized in that: In the step (1), the reaction temperature is -5 to 25°C.

4. The method for preparing triphenylamine derivatives based on phenothiazine according to claim 2, characterized in that: In the step (2), tetrakis(triphenylphosphine)palladium is used as a catalyst.

5. The method for preparing triphenylamine derivatives based on phenothiazine according to claim 2, characterized in that: In the step (2), the molar ratio of the intermediate represented by formula IV to the triphenylamine-4-boric acid represented by formula V is 1:3-4.

6. Use of the phenothiazine-based triphenylamine derivative according to claim 1 or the phenothiazine-based triphenylamine derivative prepared by the preparation method according to any one of claims 2 to 5 in the preparation of electrochromic materials.

7. A phenothiazine-based triphenylamine conductive polymer using the phenothiazine-based triphenylamine derivative according to claim 1 or the phenothiazine-based triphenylamine derivative prepared by the preparation method according to any one of claims 2 to 5 as a monomer, characterized in that: As shown in Formula VI: In Formula VI, n represents the average degree of polymerization, and n is 10-2000.

8. The method for preparing a triphenylamine-based conductive polymer based on phenothiazine according to claim 7, characterized in that: The following steps are involved: S1: dissolving the phenothiazine-based triphenylamine derivative represented by formula I and a supporting electrolyte in a solvent; S2: The phenothiazine-based triphenylamine derivatives shown in Formula I are polymerized into a film by a cyclic voltammetry electrochemical method to obtain the phenothiazine-based triphenylamine conductive polymer shown in Formula VI.

9. The method for preparing a triphenylamine-based conductive polymer based on phenothiazine according to claim 8, characterized in that: The parameters of the cyclic voltammetry electrochemical method in step S2 include: a voltage of 0 to 1.5 V, and a polymerization cycle of 11 to 15 cycles.

10. Use of the phenothiazine-based triphenylamine conductive polymer according to claim 7 or the phenothiazine-based triphenylamine conductive polymer prepared by the preparation method according to any one of claims 8 to 9 in the preparation of electrochromic electrodes.

Citation Information

Patent Citations

  • Poly(triphenylamine-phenothiazine) dye and application thereof

    CN103937292A

  • Electrochromic polymer, electrochromic composition and electrochromic display element

    JP2019172724A